EL RAY-GRASS ITALIANO DE SECANO EN LA DEHESA EXTREMEÑA (II Reunión Ibérica de Pastos y Forrajes Badajoz, 1989)
Rain fed Italian Ray-Grass considerably increases stocking rate. It permits ten times the stocking rate of non-fertilized pasture and five times that of fertilized pastures. It is a crop equally suitable for grazingsheep or cattle. The cost per feed unit can be estimated in 8 Pts (1.987). Stocking rate is 22,62 mediterranean sheep units. It is a very interesting crop as it improves productivity- of extremeñan "dehesa" with low man-power needs